Pretibial myxedema, white fibrous papulosis, eruptive syringomas: a hypothyroidism case report. - Ting, Tian; Ru-zhi, Zhang (European Journal of Pediatric Dermatology, 2015)
Pretibial myxedema (PM), white fibrous papulosis and eruptive syringomas are three uncommon skin disorders. We present a 24-year-old woman affected by hypothyroidism and presenting with all the above mentioned skin lesions. Enormous lumps on both lower limbs, thyroid acropachy and the histopathologic examination of one lump confirmed the diagnosis of PM. White fibrous papulosis and eruptive syringomas were diagnosed clinically.